RANCANG BANGUN PEMBANGKIT LISTRIK TENAGA SURYA UNTUK PENETASAN TELUR AYAM KAMPUNG - riny sulistyowati; Dio Indra Bayu (Universitas Nusa Cendana, 2026)
Electric power is essential for daily activities; however, power outages frequently disrupt electricity supply, particularly for small-scale applications such as egg incubation in free-range poultry farming. The incubation process requires continuous electrical energy to maintain heat using a 15-watt lamp for approximately 21 days. To address this issue, alternative energy sources, especially solar energy, can be utilized through photovoltaic (PV) systems. However, PV systems inherently produce unstable output voltage due to fluctuations in solar irradiance, which may affect battery charging performance. To overcome this limitation, a Buck-Boost converter is implemented to regulate and stabilize the PV output voltage. In addition, temperature and humidity sensors are integrated into the incubator system to ensure optimal environmental conditions for egg hatching. Experimental results show that the Buck-Boost converter successfully stabilizes the PV voltage at 14 V, with an average current of 1.5 A in the first week, and 1.4 A in both the second and third weeks. Furthermore, the incubator maintains an average temperature of 37°C and humidity of 56%, which fall within the recommended range for successful egg hatching. These results indicate that the proposed system is capable of providing a stable energy supply while maintaining suitable incubation conditions.